The Long-Run Relationship Between Real Exchange Rates and Real Interest Rate Differentials : A Panel Study - Nagayasu, Jun (IMF Working Papers; Working Paper ;, 1999)
This paper empirically examines the long-run relationship between real exchange rates and real interest rate differentials over the recent floating exchange rate period, using a panel cointegration method, with data for a set of industrialized countries. The paper finds evidence of statistically significant long-run relationships and plausible point estimates, which contrasts with much existing evidence. The failure of others to establish such relationships may reflect the estimation method they use rather than any inherent deficiency of the fundamentals-based models.